Introducing world Christianity - Farhadian, Charles E. 1964-. (Chichester, West Sussex Malden, MA Wiley-Blackwell, 2012)
"This is an engaging multidisciplinary introduction to the worldwide spread and impact of Christianity. Bringing together chapters from leading scholars in history, sociology, anthropology, and religious studies, this book examines the major transformations in contemporary societies brought about through the influence of Christianity. Each chapter shows how the broad themes within Christianity have been adopted and adapted by Christian denominations within each major region of the world. So, the book paints a global picture of the impact of Christianity, enriched by detailed historic and ethnographic material for each particular region. Throughout, the chapters examine Protestant, Evangelical, Catholic and Orthodox forms of Christianity. However, the approach is non-theological, focusing on the impact of and response to Christianity, rather than questions of faith. The combination of broader perspectives and deep analysis of particular regions, illuminating the social, cultural, political, and religious features of changes brought about by Christianity, makes this book essential reading for students of world Christianity"-- Provided by publisher.
Middle Eastern and North African Christianity : persisting in the lands of Islam / Heather J. Sharkey -- Christian belongings in East Africa : flocking to the churches / Ben Knighton -- West African Christianity : padres, pastors, prophets, and Pentecostals / Ogbu Kalu -- Christianity in Southern Africa : the aesthetics of well-being / Frederick Klaits -- Christianity in Western Europe : mission fields, old and new? / Simon Coleman -- Christianity in Eastern Europe : a story of pain, glory, persecution, and freedom / Peter Kuzmic -- Christianity in South Asia : negotiating religious pluralism / Arun Jones -- Christianity in Southeast Asia : similarity and difference in a culturally diverse region / Barbara Watson Andaya -- Christianity in East Asia : evangelicalism and the March first independence movement in Korea / Timothy S. Lee -- Christianity in North America : changes and challenges in a land of promise / Kevin J. Christiano -- Central America and the Caribbean : Christianity on the periphery / Virginia Garrard-Burnett -- Christianity in Latin America : changing churches in a changing continent / Samuel Escobar -- Brazilian charisma : pentecostalized Christianity in Latin America's largest nation / R. Andrew Chesnut -- Christianity in Australia and New Zealand : faith and politics in secular soil / Marion Maddox -- Christianity in Polynesia : transforming the islands / Ian Breward -- Christianity in Micronesia : the interplay between church and culture / Francis X. Hezel -- Christianity in Melanesia : transforming the warrior spirit / Garry W. Trompf.
Machine generated contents note: Dedication.Contents.List of Contributors.Map of World Christianity.Preface (Robert W. Hefner).Acknowledgments.Introduction (Charles E. Farhadian).Part I: AFRICA.1: Middle Eastern & North African Christianity: Persisting in the Lands of Islam (Heather Sharkey).2: Christian Belongings in East Africa: Flocking to the Churches (Ben Knighton).3: West African Christianity: Padres, Prophets, Pastors, and Pentecostals (Ogbu Kalu).4: Christianity in Southern Africa: The Aesthetics of Well-Being (Frederick Klaits).Part II: EUROPE.5: Christianity in Western Europe: Mission Fields, Old and New? (Simon Coleman).6: Christianity in Eastern Europe: A Story of Pain, Glory, Persecution, and Freedom (Peter Kuzmic).Part III: ASIA.7: Christianity in South Asia: Negotiating Religious Pluralism (Arun Jones).8: Christianity in Southeast Asia: Similarity and Difference in a Culturally Diverse Region (Barbara Watson Andaya).9: Christianity in East Asia: Evangelicalism and the March First Independence Movement in Korea (Timothy S. Lee).Part IV: AMERICAS.10: Christianity in North America: Changes and Challenges in a Land of Promise (Kevin J. Christiano).11: Central America and the Caribbean: Christianity on the Periphery (Virginia Garrard-Burnett).12: Christianity in Latin America: Changing Churches in a Changing Continent (Samuel Escobar).13: Brazilian Charisma: Pentecostalized Christianity in Latin America's Largest Nation (R. Andrew Chesnut).Part V: THE PACIFIC.14: Christianity in Australia and New Zealand: Faith and Politics in Secular Soil (Marion Maddox).15: Christianity in Polynesia: Transforming the Islands (Ian Breward).16: Christianity in Micronesia: The Interplay Between Church and Culture (Francis X. Hezel).17: Christianity in Melanesia: Transforming the Warrior Spirit (Garry W. Trompf).Conclusion: World Christianity: It's History, Spread, and Social Influence (Robert D. Woodberry)
Includes bibliographical references and index.
Keywords: Christianity